2020
DOI: 10.3390/su12041587
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Compacted Soil Layers in Northeast China due to Freezing-Thawing Processes

Abstract: Soil compaction has become a global concern that reduces soil quality and may jeopardize agricultural sustainability. The objective of this study is to evaluate if the freezing-thawing process can alleviate the negative effects of soil compaction during overwinter time in Northeast China. The field experiment was a split plot design including two surface treatments (bare and mulch) and three compaction levels (low, moderate, and high compactions with initial bulk densities of 1.2, 1.4 and 1.6 g cm −3 ). Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…A study has revealed a 59% reduction in penetration resistance on a compacted clay soil at a 20-30 cm depth due to freezing and thawing (Jabro et al, 2014). The same trend was observed for macroporosity with increases of up to 388% (Wang et al, 2020a) due to the freezing and thawing of compacted clay soils in the upper soil layer (0-25 cm depth).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…A study has revealed a 59% reduction in penetration resistance on a compacted clay soil at a 20-30 cm depth due to freezing and thawing (Jabro et al, 2014). The same trend was observed for macroporosity with increases of up to 388% (Wang et al, 2020a) due to the freezing and thawing of compacted clay soils in the upper soil layer (0-25 cm depth).…”
Section: Discussionmentioning
confidence: 70%
“…In soils with a high clay content, annual freezing and thawing may decrease soil compaction in the upper soil layer (< 30 cm) which is equally as effective as soil tillage (Jabro et al, 2014;Wang et al, 2020a). Other studies that were performed on topsoils with a similar clay content as the one examined in our study show that annual freezing-thawing increases pore space, reduces bulk density and aggregate stability and also increases the porosity and hydraulic conductivity (Gameda et al, 1987;Jabro et al, 2014;Kvaernø and Øygarden, 2006;Rasmussen, 1999;Wang et al, 2020a;Wang et al, 2020b). A study has revealed a 59% reduction in penetration resistance on a compacted clay soil at a 20-30 cm depth due to freezing and thawing (Jabro et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The limited impacts of CC grazing on soil compaction may be due to the following mechanisms: Because CCs can reduce soil bulk density and penetration resistance in some cases, growing CCs could offset some of the grazing CC‐induced increases in soil compaction (George et al., 2013; Kelly et al., 2021). Freeze‐thaw cycles and wetting and drying cycles could naturally alleviate soil compaction (Cui et al., 2014; Jabro et al., 2014; Wang et al., 2020). Manure return from grazing animals can increase soil organic matter, potentially mitigating compaction risks (Rakkar & Blanco‐Canqui, 2018).…”
Section: Impacts Of Grazing Cover Crop On Soil Propertiesmentioning
confidence: 99%
“…China has the third-largest frozen ground region in the world, and frozen ground covers about 56.3% of the land area in China [ 1 , 2 ]. Climate change has greatly affected the infrastructure in frozen ground locations, causing problems such as mud pumping-induced cracks and frost-related heaving on roads, and landslides induced by freeze–thaw [ 3 , 4 , 5 , 6 ]. Meanwhile, the second-largest frozen ground region and the largest carbonate-stained land area, of approximately 3.2 × 10 4 km 2 , is located in Northeast China.…”
Section: Introductionmentioning
confidence: 99%